A new locality with ctenochasmatid pterosaurs (Pterosauria: Pterodactyloidea) in the Atacama Desert, Northern Chile - Alarcón Muñoz, Jhonatan Andrés (2022)
We describe a new locality with ctenochasmatid pterosaurs found in a tidal estuarine paleoenvironment of the Quebrada Monardes Formation (Lower Cretaceous). The new locality, which is named “Cerro Tormento”, is in Cerros Bravos in the northeast Atacama region, Northern Chile. Here, we describe four cervical vertebrae, one of them belonging to a small individual, the impression of a right scapulocoracoid, a left coracoid, an impression of a left humerus, an incomplete left humerus, a distal fragment of the right humerus, and impressions of a left femur and tibiotarsus. The presence of three humeri and a cervical vertebra belonging to a small pterosaur indicate that these materials represent more than one individual. The cervical vertebrae present diagnostic traits shared with ctenochasmatid pterosaurs, such as elongated vertebral centra, with integrated neural arch, low neural spines, and dorsally located neural canal. It is currently not possible to determine if there are one or more species represented. This finding is the second geographic occurrence of pterosaurs of the clade Ctenochasmatidae in the Atacama region, although it is currently uncertain if ctenochasmatids from both locations were contemporaneous. This suggests that the clade Ctenochasmatidae was widespread in what is now northern Chile. In addition, the presence of bones belonging to more than one individual preserved in Cerro Tormento suggest that pterosaur colonies were present at the southwestern margin of Gondwana during the Early Cretaceous.